One year of anatomy teaching and learning in the outbreak: Has the Covid‐19 pandemic marked the end of a century‐old practice? A systematic review. Issue 2 (21st January 2022) - Papa, Veronica; Varotto, Elena; Galli, Massimo; Vaccarezza, Mauro; Galassi, Francesco M.
Abstract: At the end of 2019, the Covid‐19 pandemic spread caused restrictions in business and social spheres. Higher education was also severely affected: universities and medical schools moved online to distance learning and laboratory facilities closed. Questions arise about the long‐term effects of this pandemic on anatomical education. In this systematic review, the authors investigated whether or not anatomical educators were able to deliver anatomical knowledge during this pandemic. They also discuss the challenges that anatomical education has faced over the last year. The search strategy was conducted between July 2020 and July 2021. Two hundred and one records were identified, and a total of 79 studies were finally included. How best to deliver anatomy to students remains a moot point. In the last years, the advent of new technologies has raised the question of the possible overcoming of dissection as the main instrument in anatomical education. The Covid‐19 pandemic further sharpened the debate. Remote learning enhanced the use of technologies other than cadaveric dissection to teach anatomy. Moreover, from the analyzed records it appears that both from students' perspective as well as teachers' there is a clear tear between those who endorse dissection and those who believe it could be easily overcome or at least integrated by virtual reality and online learning. The authors strongly believe that the best anatomy teaching practice requires the careful adaptation of resources and methods. Nevertheless, they support cadaveric dissection and hope that it will not be replaced entirely as a result of this pandemic.